Controversial Focus and International Consensus Interpretation of Medical and Interventional Therapy for Type B IMH - Yucheng Gao; Hongwei Lei (International Journal of Biology and Life Sciences, 2026)
Type B Intramural Aortic Hematoma (IMH) is an important subtype of acute aortic syndrome, and its clinical management has long been debated between conservative medical therapy and interventional therapy via Thoracic Endovascular Aortic Repair (TEVAR). Medical therapy mainly relies on strict blood pressure and heart rate control, advocating conservative management and long-term follow-up observation for uncomplicated cases. By contrast, interventional therapy features minimal trauma, which can effectively prevent disease progression and reduce the risk of long-term complications in the management of complicated cases. Nevertheless, divergent opinions still exist regarding its indications, timing of intervention, and the balance between risks and benefits. This article comprehensively summarizes the controversial issues concerning medical and interventional therapy for Type B IMH. Based on international multidisciplinary consensus documents issued in recent years, it analyzes the respective scope of application, clinical significance and underlying decision-making logic of the two therapeutic approaches, so as to formulate individualized treatment strategies for patients at different risk levels and provide theoretical support for standardized clinical diagnosis and treatment.